2018
DOI: 10.1177/2325967118755330
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction in Skeletally Immature Patients: Early Results Using a Hybrid Physeal-Sparing Technique

Abstract: Background:Reconstruction of the anterior cruciate ligament (ACL) in the skeletally immature patient is frequently performed in hopes of preventing new or additional chondral damage and meniscal injuries. Patients within a few years of skeletal maturity are more at risk for ACL injuries than prepubescent patients, about whom several physeal-sparing techniques have been described. Reconstruction techniques in the former higher risk group need to be better understood.Purpose:To review a series of adolescent pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…Three of the identified PROMs were specific measures for pediatric patients—that is, the Pedi-IKDC, 41 Knee injury and Osteoarthritis Outcome Score for Children (KOOS-Child), 70 and the Hospital for Special Surgery Pediatric Functional Activity Brief Scale (HSS Pedi-FABS). 22 These PROMs were used in 5, 40,61,93,98,99 1, 85 and 1 16 of the 68 studies, respectively. Of the 5 studies including the Pedi-IKDC as an outcome measure, 1 was published in 2013, 61 1 in 2015, 98 1 in 2017, 93 and 2 in 2018 40,99 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three of the identified PROMs were specific measures for pediatric patients—that is, the Pedi-IKDC, 41 Knee injury and Osteoarthritis Outcome Score for Children (KOOS-Child), 70 and the Hospital for Special Surgery Pediatric Functional Activity Brief Scale (HSS Pedi-FABS). 22 These PROMs were used in 5, 40,61,93,98,99 1, 85 and 1 16 of the 68 studies, respectively. Of the 5 studies including the Pedi-IKDC as an outcome measure, 1 was published in 2013, 61 1 in 2015, 98 1 in 2017, 93 and 2 in 2018 40,99 .…”
Section: Resultsmentioning
confidence: 99%
“…In our review, this scale was identified as an outcome measure in 2 of the included studies—both published in 2018. 40,99 The psychological aspect of return to sport is important to include in the evaluation of the pediatric patient; however, to our best knowledge, the current version of the ACL-RSI was not developed for children and has not been validated in pediatric patients, which is why future work should address this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique provides an anatomic reconstruction that minimizes the risk of physeal damage but is also reproducible and less technical than the aforementioned physeal-sparing techniques. Willson et al posits this technique provides high success rates with low morbidity in adolescents nearing skeletal maturity ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 To stabilize the knee, different surgical techniques have been developed for ACL reconstruction in the pediatric population. 3 , 4 , 5 , 6 According to published results, 7 the use of a hybrid anatomic technique, intra-epiphyseal in the femur and transphysis in the tibia, has been recommended as the technique of choice to reconstruct the ACL in these patients. Despite the favorable results, this technique is not exempt from complications.…”
mentioning
confidence: 99%